Ethnographic profile of Pauri Bhuinya - Jena, Surendra Kumar (New Delhi : Maya Publishing House, 2023)
Study conducted in Keonjhar District of Odisha, India.
Includes bibliographical references (pages 180-188).
Keywords: Paudi Bhuyan (Indic people) -- India -- Keonjhar (District) -- Social conditions; Paudi Bhuyan (Indic people) -- India -- Keonjhar (District) -- Economic conditions; Paudi Bhuyan (Indic people) -- India -- Keonjhar (District) -- Religion; Keonjhar (India : District) -- Religious life and customs; India -- Keonjhar (District)